2014 IEEE Conference on Control Applications (CCA) 2014
DOI: 10.1109/cca.2014.6981353
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and control of gas supply for burners in gas-fired industrial furnaces

Abstract: In gas-fired industrial furnaces, gas burners are typically used for heating of a load. The heating process inside the furnace has a strong influence on the product quality of the load. For accurate control of the load temperature, highperformance subordinate control of the mass flow of natural gas and air to the burners is crucial. For this purpose, a mathematical model of the fuel branch of a furnace is derived based on first principles. The model is validated by means of measurement data from a real plant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Measurement data taken from the plant was used to validate the model, which was indicated as feasible. The results from a simulation study indicated a better control performance by the proposed controller, when compared to a feedforward control strategy alone [74]. The approach to this study solution showed a different perspective to maintaining furnace temperature stability by considering the gas supply pipe network characteristics.…”
Section: Strommer Et Al [74]mentioning
confidence: 92%
See 4 more Smart Citations
“…Measurement data taken from the plant was used to validate the model, which was indicated as feasible. The results from a simulation study indicated a better control performance by the proposed controller, when compared to a feedforward control strategy alone [74]. The approach to this study solution showed a different perspective to maintaining furnace temperature stability by considering the gas supply pipe network characteristics.…”
Section: Strommer Et Al [74]mentioning
confidence: 92%
“…This was achieved by applying first principles to mathematically model the fuel branch of the furnace. A combination of a two degrees-of-freedom control strategy and a simple PID-feedback controller was proposed for the furnace to complement the study [74].…”
Section: Strommer Et Al [74]mentioning
confidence: 99%
See 3 more Smart Citations